Design of Computer-Based Paliative Nursing and Paliative Screening Documentation Information Systems - Emilia Puspitasari Sugiyanto; Mulyono Mulyono (Indonesian Journal of Global Health Research, 2023)
The development of health information systems is currently quite rapid, one of which is the nursing care documentation system, including psychiatric nursing. Several psychiatric hospitals now use a lot of computer-based documentation systems and some are even Android-based. Health education is a producer of graduates of health workers, which is expected to be able to meet the needs of graduate users. For this reason, every health graduate must be able and skilled in carrying out the nursing care documentation process. The purpose of this research is to design a psychiatric nursing documentation that can be used in health education. This type of research is design research. The research activity began with the creation of a diagram of the nursing care documentation process flow system. After the flowchart system is made, the researcher begins to design a system that is in accordance with the flowchart design. The final results of the research on the design of the psychiatric nursing care documentation system design. The results of this study can be used to study computer-based mental nursing documentation.